2021
DOI: 10.3897/aiep.51.74082
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth estimates from three hard parts of the spotted catfish, Arius maculatus (Actinopterygii: Siluriformes: Ariidae), in Songkhla Lake, Thailand’s largest natural lake

Abstract: The spotted catfish, Arius maculatus (Thunberg, 1792), is a euryhaline fish that is economically important in the Indo-West Pacific. Population dynamics studies and stock assessments of this species have focused on marine stocks, but not those from fresh water. In this study, the age and growth of A. maculatus were, therefore, investigated for the inland stock in Songkhla Lake, Thailand. A total of 213 individuals ranging between 35 and 238 mm TL were used. The length–weight relation indicated positive allomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Genidens genidens and G. genidens from the CIELC, which makes it possible to determine this species' ages, a fact corroborated by Carvalho et al (2014), Santificetur et al (2017), Azevedo et al (2019), Morais and Azevedo (2021). The use of lapilli otoliths for age estimation in other sea catfish species has also been made by Reis (1986), Cheraghi-Shevi et al (2015), Al-Husaini et al (2021) and Phaeviset et al (2021), andHauser et al (2018) applied this method to freshwater catfishes.…”
Section: Cathorops Spixiimentioning
confidence: 81%
See 1 more Smart Citation
“…Genidens genidens and G. genidens from the CIELC, which makes it possible to determine this species' ages, a fact corroborated by Carvalho et al (2014), Santificetur et al (2017), Azevedo et al (2019), Morais and Azevedo (2021). The use of lapilli otoliths for age estimation in other sea catfish species has also been made by Reis (1986), Cheraghi-Shevi et al (2015), Al-Husaini et al (2021) and Phaeviset et al (2021), andHauser et al (2018) applied this method to freshwater catfishes.…”
Section: Cathorops Spixiimentioning
confidence: 81%
“…It has already been observed that, in the lapillus otolith, the narrow opaque zones represent slow growth, while the wide hyaline or translucent zones represent rapid growth. For instance, some researchers have used the lapilli otolith to estimate the age and growth of ariids from different regions, such as Bagre panamensis, from the United States, California (Maldonado-Coyac et al, 2021), Arius maculatus, from Thailand (Phaeviset et al, 2021), and Plicofollis tenuispinis, Netuma bilineata, Netuma thalassina, and Plicofollis dussumieri, from Kuwaiti waters (Al-Husaini et al, 2021). In Brazil, some researchers have studied G. genidens and G. barbus (Reis, 1986;Oliveira and Novelli, 2005;Gibbs et al, 2013;Maciel et al, 2018).…”
mentioning
confidence: 99%
“…Estimation of fish growth can provide a valuable understanding of its life history, and can be further used to formulate optimum fishing regulations for sustaining stocks [28]. The von Bertalanffy model was generally considered to be the most reliable candidate model for fish stocks in a mathematical sense [29].…”
Section: Growth Characteristics Of S Curriculusmentioning
confidence: 99%